Aprendizagem social e o tornar-se voluntário dirigente à luz do processo de participação periférica legítima: um estudo de caso na rede feminina de combate ao câncer - Meneghelli, Andressa Bueno Serigato (2017)
This study addresses learning as a characteristic process of communities of practice, developing itself from the social interaction and resulting in the acquisition of a competency and in the change of the participant's identity. Taking the phenomenon from the lens of social learning and based on the theory developed from the studies of Lave and Wenger (1991) and Wenger (1998), the research adopts a qualitative approach. As research strategy, a case study was developed in the Women's Network Against Cancer, a philanthropic institution, founded on March 18, 1954, which currently has the work of approximately 400 volunteers, working in several sectors inside and outside of Erasto Gaertner Hospital, in the city of Curitiba (Parana, Brazil). This study aimed to understand the learning process of becoming a volunteer leader in the Women's Network focused on the process of Legitimate Peripheral Participation. For conducting the research, 28 narrative interviews were carried out with active volunteers, with the practice of learning to become a volunteer leader as unit of analysis and level of analysis, accessed through direct observation. The research is a descriptive study and the methodology used for treatment and analysis of empirical material was narrative analysis. Results show that learning to become a leader in the communities of practices of the Women's Network starts from apprentice admission, since before becoming a leader one must become a volunteer, and involves: (1) prove to be a humble and committed person; (2) demonstrate that the practice of volunteering was understood; (3) transform the identity from practice becoming a field or production volunteer; (4) have the competence recognized so that participation becomes legitimate; (5) be appointed or elected to a management position and assume the role of leader or head in the related community of practice; (6) start a new process of legitimate peripheral participation. The analysis also demonstrates that volunteers are reluctant to take management positions because of their perception of becoming a leader, which would mean losing the focus of volunteering.